Improving Grain sector Climate-Smart Awareness and decision-making - International Institute of Tropical Agriculture; Sustainable Food Lab; CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Nile Breweries Limited, a subsidiary of AB InBev, has sought to improve their supply chains of sorghum and barley through local sourcing and sustainability commitments. This outcome story shares how Nile Breweries Limited leveraged the Guide to Assessing Climate Resilience in Smallholder Supply Chains, part of the USAID Feed the Future Learning Community for Supply Chain Resilience, to further understand their climate risks and the possible interventions available to build resilience against climate change. This outcome story also highlights the challenge of private sector actors to justify resource use to combat climate change and the complexity of working with smallholder farmers. This case was developed by the Sustainable Food Lab, in 2018 and draws from qualitative interviews with Nile Breweries and partner TechnoServe.